Do the positions of trimethyl groups on phthalocyanine photosensitizers improve their photochemical and photophysical properties? - ALTUN, SELÇUK; ODABAŞ, ZAFER (ELSEVIER SCIENCE SA, 2017)
The synthesis of novel highly soluble and non-aggregated metal-free and zinc(II) phthalocyanines containing four 2,3,5-trimethylphenoxy groups was achieved by starting phthalonitrile compounds. The phthalocyanines were characterized by elemental analysis, infrared, ultraviolet-visible and matrix assisted laser desorption/ionization time-of-flight mass spectroscopic techniques. Their photochemical and photophysical properties were also investigated in N,N-dimethylformamide. In addition, the influences of position of methyl groups on phenoxy unit and nature of metal in phthalocyanine cavity on photophysical and photochemical properties were investigated by comparing with previous analogues (phthalocyanines with 2,3,6-trimethylphenoxy and 2,4,6-trimethylphenoxy groups). (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; 2,3,5-Trimethylphenoxy; Photosensitizer; Photophysical; Photochemical; SUBSTITUTED ZINC PHTHALOCYANINES; PHOTODYNAMIC THERAPY; SOLAR-CELLS; THIN-FILMS; METAL-FREE; BEARING; METALLOPHTHALOCYANINES; STABILITY; MECHANISM; BEHAVIOR